Dynamic land use efficiency and human-land relationship in traditional industrial cities - Kong, Xianglong; Wu, Yutong; Cui, Peng; Sun, Yiwen; Wei, Guangpu (Frontiers in Environmental Science, 2025)
Indroduction Northeast China is a traditional industrial region. Studying the dynamic land utilization efficiency during urbanization is crucial for understanding the human-land relationship in cities facing economic decline.MethodsUsing land utilization and population data from 2000 to 2020, a dynamic land utilization efficiency index was developed to identify patterns in land utilization dynamics at the district and county level and assess the coordination of human-land relationships at the municipal level. The spatial structural relationships among districts and counties are analysed using the Getis-Ord Gi* statistical model, while the co ordination mechanisms of human-land interactions are explored through the Kaya identity and the Logarithmic Mean Divisia Index (LMDI).ResultsThe results demonstrate that 40.9% of counties suffer from low land utilization efficiency. 57.6% of cities experience simultaneous population decline and expansion of urban-rural construction land. The de-industrialization process in the region is not limited to a shift toward the service sector. 70.5% of cities exhibit significant characteristics of farmland restoration and reforestation during the process of urban and rural construction land reduction. Overall, the complex relationship between population migration and land use efficiency has a significant impact on the urban development patterns in the three northeastern provinces.DiscussionNet population inflow has not significantly improved land use efficiency, and the decrease in the proportion of permanent residents, along with the increase in the floating population, are key factors influencing the changes in urban-rural construction land. This study reveals the spatial differentiation of land use efficiency and its complex interaction with human-land relationships during the de-industrialization process, providing a theoretical basis for land management and regional sustainable development in traditional industrial cities.